Correlation of histamine-2 receptor antagonist (H2RA) and proton pump inhibitor (PPI) to the platelet count in patient with dengue viral infection - Riyadi Adrizain; Maharani Simanjuntak; Andri Rezano (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Thrombocytopenia is often associated with clinically worse outcomes in dengue viral infection (DVI) patients. Histamine-2 receptor antagonist (H2RA) and proton pump inhibitor (PPI) have been reported to induce thrombocytopenia. These drugs are administered to DVI patients due to misinterpretation of abdominal pain. The study aimed to evaluate the correlation between H2RA and PPI administration with thrombocytopenia event on hospitalized DVI patients. An analytical retrospective cross-sectional study was conducted using medical records of the patient admitted by final diagnosed DVI in seven major hospital in Bandung from January 1st to December 31st, 2015. Patients were separated into two groups i.e. with and without H2RA and PPI. Pearson point biserial analysis was then applied to evaluate the correlation of each drug administration to platelet count of DVI.  A total of 4005 patients with final diagnosed DVI involved in this study. About 11.0% and 25.1% of the patients received H2RA and PPI, respectively. Mostly the DVI patients receiving H2RA (55%) and PPI (50.8%) showed the platelet count <50.000/mm3. A very weak positive correlation between the administration of H2RA (p <0.001; r=0.103) and PPI (p <0.001; r=0.138) with the low platelet count of the patients was observed. In conclusion, the administration of H2RA and PPI is correlated to the low platelet count in DVI patients. Although the correlation is weak, H2RA and PPI should be administered with caution due to its thrombocytopenia side effect.